Healthy donor hematopoietic stem cell mobilization with biosimilar granulocyte‐colony‐stimulating factor: safety, efficacy, and graft performance. Issue 12 (16th September 2016) - Becker, Petra; Schwebig, Arnd; Brauninger, Susanne; Bialleck, Heike; Luxembourg, Beate; Schulz, Miriam; Tsamadou, Chrysanthi; Wiesneth, Markus; Reinhardt, Peter; Mytilineos, Joannis; Seidl, Christian; Gattu, Sreekanth; et al.
Abstract : BACKGROUND: Biosimilar granulocyte‐colony‐stimulating factors (G‐CSFs) have been available in the European Union since 2008, and Sandoz' biosimilar filgrastim was approved in the United States in March 2015 for all of the reference product's indications except acute radiation syndrome. Biosimilar G‐CSFs have been largely embraced by the medical community, except for some reservations about healthy‐donor stem cell mobilization, for which use outside of clinical studies was cautioned against by some members of the scientific community. STUDY DESIGN AND METHODS: In a two‐center safety surveillance study (National Clinical Trial NCT01766934), 245 healthy volunteer stem cell donors were enrolled. Of 244 donors who began mobilization with twice‐daily Sandoz biosimilar filgrastim, 242 received a full (n = 241) or partial (n = 1) course of G‐CSF and underwent apheresis. Efficacy and safety were assessed and are reported here. RESULTS: Biosimilar filgrastim was accompanied by the typical G‐CSF class‐related adverse effects of expected frequency and severity. Median mobilization for CD34‐positive stem cells was 97/µL (range, 20‐347/µL); after one apheresis (91%) or two aphereses (9%) from all but three donors (1.2%), cell doses in excess of the typical 4 × 10 6 CD34‐positive cells/kg of the recipient had been collected (range, 3‐52 × 10 6 /kg). Biochemical and hematologic alterations were consistent with previous reports; all had normalized by the first follow‐up 1 month after mobilization. Stem cell products engrafted with typical probability and kinetics for G‐CSF‐mobilized stem cell products. CONCLUSION: These data support the use of biosimilar filgrastim for healthy‐donor stem cell mobilization as safe and effective.